A full factorial experimental design to study the effect of flavoring agents on the mechanical properties of curcumin chewing gum tablets with high solids content. (2nd April 2020) - Al Hagbani, Turki; Kamal, Mohammad M.; Nazzal, Sami
Abstract: Objective: Developing chewing gum tablets (CGTs) with high drug loads is a challenge due to the loss of mastication properties. We postulated that poor mastication properties of such gums could be improved by adjusting the concentration of liquid flavors to serve as plasticizers and consequently increase the flexibility of the elastomer in the gum base. To test this hypothesis, the objective of this work was to evaluate the effects of flavor type and concentration, and storage conditions on the textural properties of CGTs loaded with 20% curcumin (CUR) by weight. Methods: CGTs were made by directly compressing Health in Gum ® base with CUR. The resultant CGTs were characterized by single and two bites textural tests to measure their yield strength, post-bite failure rate, and compressibility. Results: Flavor concentration ( X 2 ) had a significant impact on the masticatory properties of the chewing gums, which could be ascribed to the plasticizing effect of peppermint oil. Addition of liquid flavors and storage at low temperature ( X 4 ) produced CGTs with the desirable properties of low yield strength ( Y 1 ) and post-bite structural failure rate ( Y 2 ), and high compressibility ( Y 3 ). The effect of flavors however was negated at high temperatures, especially when flavored gums were stored for extended time at 50 °C. Flavor type ( X 1 ) on the other hand had no effect on the masticatory properties of the chewing gums. Conclusions: This study concluded that it is feasible to formulate CGTs with high solids content without negatively impacting their mechanical properties by controlling the concentration of liquid flavors.